2017
DOI: 10.1016/j.bjorl.2016.06.008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of melatonin and vitamin C treatment on the experimentally induced tympanosclerosis: study in rats

Abstract: Melatonin increases total antioxidant status level and might have some effect on tympanosclerosis that develops after myringotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Three days after injection of inactivated S. pneumoniae, yellowish serous fluid was found in the middle ear cavity of most rats, but there was generally no purulent fluid. Long-term exudation of inflammatory substances stimulates tympanosclerosis in the middle ear mucosa; meanwhile, perforation of the tympanic membrane during injection promotes the formation of a high-oxygen environment in the tympanum, which in turn induces accumulation of oxygen free radicals and promotes tympanosclerosis (30). Perforation of the tympanic membrane caused by puncture usually heals within 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Three days after injection of inactivated S. pneumoniae, yellowish serous fluid was found in the middle ear cavity of most rats, but there was generally no purulent fluid. Long-term exudation of inflammatory substances stimulates tympanosclerosis in the middle ear mucosa; meanwhile, perforation of the tympanic membrane during injection promotes the formation of a high-oxygen environment in the tympanum, which in turn induces accumulation of oxygen free radicals and promotes tympanosclerosis (30). Perforation of the tympanic membrane caused by puncture usually heals within 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have not measured oxidative stress markers in the present study, it has been shown that formation of free oxygen radicals is important for the development of tympanosclerosis within the middle ear (3). Researches have emphasized that melatonin, a potent antioxidant, inhibits sclerosis (11). Hence, antioxidant treatment may reduce tympanosclerosis formation.…”
Section: Discussionmentioning
confidence: 99%